Proportionality Test in International Investment Agreements: Balancing Regulatory Sovereignty and Investor Protection - Syifa Rizky Almasari (Nusantara: Journal of Law and Islamic Law, 2026)
This study analyzes the jurisdictional clash between investor protection and host state regulatory sovereignty within modern international investment agreements. While new generation treaties incorporate explicit right to regulate provisions, arbitral tribunals frequently undermine these reforms through orthodox interpretations, creating a systemic arbitral backlash. Employing a normative legal methodology with statutory, conceptual, and case approaches, this research investigates the urgency of integrating the proportionality test into investor state dispute settlement. The systemic integration principle from the Vienna Convention on the Law of Treaties legitimizes this methodological transplantation. Results indicate that adopting proportionality as a mandatory standard of review effectively limits arbitral overreach, converting the conditional defenses of the state into inherent police powers. Contextualized within the new Model Bilateral Investment Treaty of Indonesia, this structural adaptation proves empirically vital. Ultimately, aligning national textual reforms with supranational proportionality analysis provides an equitable framework, successfully harmonizing absolute investment protections with public welfare mandates.